Interactions of Lipid Polar Headgroups with Carbendazim Fungicide - Furini, Leonardo N. [UNESP]; Morato, Luis F. C. [UNESP]; Olivier, Danilo S. [UNESP]; Lemos, Monique [UNESP]; Feitosa, Eloi [UNESP]; Constantino, Carlos J. L. [UNESP] (Amer Scientific Publishers, 2019)
Carbendazim (MBC) is a fungicide widely used in agriculture which allows the high productivity of several cultures, a necessary condition considering the growing of the world population. Moreover, MBC has environmental impact mainly on the soil and water sources, and consequently, on animal and human lives. However, even though the toxicity of fungicides is well established, their action mechanism in cell membranes are not completely understood. Herein, we investigate the interaction of different polar headgroups: dimethyldioctadecylammonium bromide (DODAB), 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and 1,2-dipalmitoyl-sn-glycero-3-phospho-(1'-rac-glycerol) (DPPG); and different chain unsaturation degrees DPPC, 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) with MBC. Lipid monolayers at the air/water interface were applied as mimetic systems of cell membranes to investigate the interaction with MBC dissolved in the ultrapure water subphase. It was found that the interaction is driven preferably by electrostatic forces of the headgroups, with higher affinity for DODAB (cationic), intermediate for DPPC (zwitterionic), and absent for DPPG (anionic), considering the monolayer in the condensed phase. DODAB-MBC electrostatic interaction was consistent with FTIR (cast films). We also investigated giant unilamellar vesicles (GUVs) of zwitterionic lipids (DPPC, POPC, and DOPC) with distinct chain unsaturations in the presence of MBC by confocal microscopy and molecular dynamic (MD) simulations. The results indicate that, unlike the chain unsaturation, the polar headgroups play key role on the lipid-MBC interaction.
Keywords: Carbendazim; Langmuir Film; Lipid Vesicle; Molecular Interaction